2009
DOI: 10.1007/s11146-009-9222-y
|View full text |Cite
|
Sign up to set email alerts
|

REIT Stock Splits and Liquidity Changes

Abstract: REIT stock split, Liquidity, Attention-grabbing, Signaling, G32,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…An examination study introduced by Huang et al, (2011), to test the effect of the stock splits on liquidity change. They found that the liquidity of the stock splits has been improved almost the period of the stock splits announcement and the period after the ex-dates the stock prices have given back to the prices level as before the stock splits.…”
Section: The Impact Of the Stock Splits On Share Pricesmentioning
confidence: 99%
“…An examination study introduced by Huang et al, (2011), to test the effect of the stock splits on liquidity change. They found that the liquidity of the stock splits has been improved almost the period of the stock splits announcement and the period after the ex-dates the stock prices have given back to the prices level as before the stock splits.…”
Section: The Impact Of the Stock Splits On Share Pricesmentioning
confidence: 99%
“…Egyptian Exchange percentage exchange between (Stock Split -Market Value Change Rate) for Travel and Leisure Index during the Period 2010:2018 Accordingly, it is obvious from table (3) that Stock Split works to increase Market Value like: El Wadi Co. For Touristic Investment that indicates 7.65%, Rowad Tourism (Al Rowad) that indicates 10.9%, Misr Hotels that indicates 23.4%, Marsa Marsa Alam for Tourism Development that indicates 14.8%, Egyptian International Tourism Resorts 6.16%, Golden Coast Company that indicates 10.6%, Sharm Dreams Co. For Tourism Investment that indicates 8.91%, Trans Oceans Tours that indicates 12.9%, and Golden Pyramids Plaza that indicates 14.4%. This point is supported by the study conducted byBandyopadhyay et al, (2010);Huang et al, (2011), Waweru et al, (2012; Tabibian (2013); Agara, (2014);Chowdhury (2014);Nyaga, (2017). This proves that Stock Split works to increase Market Value and encourages investors to invest in Hotels and Tourism Index and attract more investors to finance in tourism and hospitality projects and future company's investment plan.…”
mentioning
confidence: 59%
“…This suggests that stock splits, being anticipated events, allow market makers and small investors to be able to predict order flows and adjust their positions accordingly. Huang et al, (2011), Waweru et al, (2012 ;Nyaga, (2017), in Nairobi Stock Market in Kenya. El Ansary andHussien (2017) in Egyptian Stock Market.…”
Section: Development Of Research Hypothesismentioning
confidence: 99%
“…Reaksi pasar modal terhadap stock splits dimulai oleh (Fama et al, 1969) yang menemukan bahwa harga saham menyesuaikan dengan datangnya informasi baru dari stock splits yang merefleksikan harga saham yang berubah setelah tanggal pengumuman dan perubahan harga saham itu berhubungan dengan tingkat efisiensi pasar. (Huang et al, 2011)menemukan bahwa stock splits dapat menarik investor karena tingkat likuiditasnya. Sementara (Waweru & Mwendwa, 2012) yang meneliti di pasar modal Nairobi menemukan bahwa harga saham meningkat setelah periode stock splits.…”
Section: Pendahuluanunclassified
“…(Campbell & Ohuocha, 2011)yang meneliti tentang "Reaction of Stock Market on Stock Dividends in Nigeria" dengan menggunakan event study dan sampel adalah perusahaan dagang yang listing pada pasar modal Nigeria tahun 2002 sd 2006 menemukan bahwa harga saham pada pasar modal Nigeria bereaksi terhadap pengumuman stock dividends setelah pengumuman namun tidak bereaksi pada sebelum pengumuman. Sedangkan (Huang et al, 2011)yang meneliti tentang "REIT Stock Splits and Liquidity Changes" menemukan bahwalikuiditas akibat stock split meningkat pada jendela pengumuman dan setelahnya likuiditas kembali pada level sebelum stock splits. Berdasarkan hasil penelitian diatas dirumuskan hipotesis pertama (H1) yaitu aksi stock dividends menyebabkan Pasar Modal Indonesia bereaksi, hipotesis kedua (H2) yaitu aksi stock splits menyebabkan Pasar Modal Indonesia bereaksi.Dan hipotesis ketiga (H3) yaitu terdapat perbedaan reaksi pasar antara stock dividens dengan stock splits.…”
Section: Reaksi Pasar Modal Atas Aksi Stock Dividends Dan Stock Splitsunclassified